2015
DOI: 10.1017/pab.2015.19
|View full text |Cite
|
Sign up to set email alerts
|

Maiasaura, a model organism for extinct vertebrate population biology: a large sample statistical assessment of growth dynamics and survivorship

Abstract: Abstract.-Fossil bone microanalyses reveal the ontogenetic histories of extinct tetrapods, but incomplete fossil records often result in small sample sets lacking statistical strength. In contrast, a histological sample of 50 tibiae of the hadrosaurid dinosaur Maiasaura peeblesorum allows predictions of annual growth and ecological interpretations based on more histologic data than any previous large sample study. Tibia length correlates well (R 2 > 0.9) with diaphyseal circumference, cortical area, and bone w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

15
196
1
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 116 publications
(214 citation statements)
references
References 77 publications
(196 reference statements)
15
196
1
2
Order By: Relevance
“…MOR 790 7-23-95-122), while a 27 m individual is at least 24 years old (D. carnegii CM 94). These growth rates are not nearly as accelerated as those recorded in some other dinosaurs -such as a 3 m body lengths within the first year in Maiasaura (Woodward et al, 2015) -but they are still consistent with rapid growth rates. In terms of historical perceptions of longevity, sauropods have run the estimation gamut -attaining maximum body size within a decade (Curry, 1999) or taking up to several centuries (and finally sexually mature at 72 years of age; Case, 1978).…”
Section: Implications Regarding Sauropod Growth Ratessupporting
confidence: 74%
See 1 more Smart Citation
“…MOR 790 7-23-95-122), while a 27 m individual is at least 24 years old (D. carnegii CM 94). These growth rates are not nearly as accelerated as those recorded in some other dinosaurs -such as a 3 m body lengths within the first year in Maiasaura (Woodward et al, 2015) -but they are still consistent with rapid growth rates. In terms of historical perceptions of longevity, sauropods have run the estimation gamut -attaining maximum body size within a decade (Curry, 1999) or taking up to several centuries (and finally sexually mature at 72 years of age; Case, 1978).…”
Section: Implications Regarding Sauropod Growth Ratessupporting
confidence: 74%
“…In exceptional ontogenetic studies, large sample sizes including representatives of multiple growth stages allow for more comprehensive histologic and morphological comparisons (e.g., Dodson, 1975;Carr, 1999;Scannella and Horner, 2010;Horner et al, 2011;Frederickson and Tumarkin-Deratzian, 2014;Woodward et al, 2015). While Morrison diplodocids are by far one of the most common of all North American dinosaur groups, taphonomic biases, stratigraphic resolution, and taxonomic uncertainties generally result in largely incomplete and less well understood individuals.…”
Section: Examination Methodsologymentioning
confidence: 99%
“…Study of these remains indicates that they represent ontogenetic developmental stages ranging from near-term embryos to early-to-late hatchlings (Grigorescu and Csiki, 2006;Benton et al, 2010;Grigorescu et al, 2010), and thus document the simultaneous presence of individuals with different body sizes and representing different age classes in the Telmatosaurus hatchling material. Despite the relatively wide size range of the limb bones (suggesting the presence of babies of different sizes in the nesting ground), these size differences do not represent a long time interval, and it is probable that these different sized neonates hatched during the same breeding season, followed by a rather rapid early ontogenetic development, as already suggested for hadrosauroids (e.g., Horner and Weishampel, 1988;Horner et al, 2000;Grigorescu and Csiki, 2006;Woodward et al, 2015).…”
mentioning
confidence: 80%
“…It was already suggested that the chance of preservation for hatchling remains is relatively high in their nesting areas. This is because here the baby skeletal elements are very abundant as a consequence of high mortality rates during the hatching period, resulting from intrinsic causes such as disease, abandonment, trampling or siblicide (e.g., Horner, 1994;Rogers and Kidwell, 2007;Brinkman et al, 2007;Woodward et al, 2015). Horner (1994) even suggested that most, if not all, baby dinosaur mortality occurred in the nesting areas, since baby dinosaur remains are extremely rare in the fossil record except in nesting grounds or accumulations reworked directly from these.…”
mentioning
confidence: 99%
See 1 more Smart Citation